"Boundary Work". (3rd October 2022) - Roginska, Maria
Abstract : The article presents the strategies that natural scientists from Central and Eastern Europe undertake to establish the demarcation between science and religion. Based on a 100 semi-structured interviews with physicists and biologists from Poland and Ukraine it demonstrates cultural differences of boundary work undertaken in the two groups. Moreover, the boundary lines between science and religion, knowledge and faith prove to be isomorphic to other boundaries (e.g. between the natural and supernatural, matter and spirit). It demonstrates further how these results can contribute to explaining the lower level of religiousness of scientists in Poland. The data collected point to a general conclusion that the lower level of religiousness of academics observed in international studies may have heterogeneous basis and forms; the impact of science on the religiousness of societies is varied and culturally conditioned.